A rapid and visible colorimetric fluorescent probe for benzenethiol flavor detection. (15th July 2019) - Wang, Hao; Wu, Xiaoming; Yang, Shaoxiang; Tian, Hongyu; Liu, Yongguo; Sun, Baoguo
Highlights: Development of a new, rapid, visible colorimetric fluorescent probe for benzenethiols. The detection limit of this fluorescent probe is 10 nM. Benzenethiol was successfully detected in real samples using the new probe. Abstract: Benzenethiols are a class of flavoring ingredients used in the food, pharmaceutical, cosmetics and chemical industries. A rapid and visible colorimetric fluorescent probe was developed for the detection of benzenethiol flavors. It provides rapid quantitative detection of benzenethiols at low levels, down to a limit of 10 nM. Test paper containing the probe changes color according to benzenethiol concentration (from colorless to pink, visible with the naked eye). The probe was also successfully used to test benzenethiol concentrations in real food samples. This study demonstrates that this novel probe can be employed as a benzenethiol testing tool.